Seasonal incidence of insect pest of banana (Musa paradisiaca) from Gangetic basin of West Bengal, India - KAR, ANAMIKA; SINGH, SANDEEP; BAURI, FATIK KUMAR; MISRA, DILIP KUMAR; PATIL, PRAKASH (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during 2018–23 at Bidhan Chandra Krishi Viswavidyalaya, Nadia, West Bengal with a view to ascertain the seasonal incidence of major insect pests and occurrence of new emerging pests of banana (Musa paradisiaca L.) crop. The study revealed that leaf and fruit scarring beetle Basilepta subcostata (Jacoby) was most dominating insect-pest followed by rugose spiralling whitefly (Aleurodicus rugioperculatus Martin). All the studied weather parameters collectively influenced 90, 87, 87 and 77% of variations in the incidence of B. subcostata (Jacoby), Odioporus longicolis (Olivier), A. rugioperculatus (Martin) and Oligonychus sapienticolus (Gupta), respectively. Barring Oligonychus sapienticolus (Gupta), all other studied insects had significant positive correlation with different weather parameters except sunshine hours that showed positive correlation with the spider mite. Besides, few insects were recorded as emerging problem of banana crop in this state like banana lace wing bug Stephanitis typica (Distant), sucking pest of banana foliage and brown tussock moth Olene mendosa (Hubner) feeding on the unfurled leaf of the seedling suckers and thus causing considerable damage.